Faste og variable omkostninger ved betalinger i Danmark - Johan Gustav Kaas Jacobsen (Danmarks Nationalbank, 2012)
– Cash are socially less costly than payment cards for all payments below DKK 29, while Dankort, the national Danish debit card, are cheaper for all other point-of-sale payments. These results are derived from calculations that divide costs of payments into fixed, variable-transaction-dependent, and variable-amount-dependent costs. Such a division makes it possible to calculate marginal costs, i.e. the social costs of one additional payment with cash and different types of payment cards, and how the marginal costs depend on the size of the payment. Furthermore, the calculations can be used to show the potential savings in terms of social cost from transferring payments from expensive to cheap types of payments. For instance, if one fourth of all larger cash payments (above DKK 200) were to be paid by Dankort instead of cash, DKK 145 million in social costs could be saved.
Keywords: 330; Zahlungsverkehr; Kreditkarte; Soziale Kosten; Dänemark